Kewajiban Memberi Biaya Penghidupan Oleh Suami Kepada Mantan Istri (Studi Komparasi Antara Hukum Islam dan Hukum Perdata) - Muh. Fahrul; Saharuddin Saharuddin; Lia Trizza Firgita Adhilia (Jurnal Litigasi Amsir, 2023)
This study aims to know and understand the husband's obligation to provide living expenses to the ex-wife and the rights of the ex-wife after divorce. The type of research in this study is Normative-empirical. The results showed the ex-husband's obligations and the wife's rights after the divorce with the provisions attached to it as previously explained. For example, there are things that make the ex-wife get the right to provide whether it is Iddah, Mut'ah, or Lampau, but there are also things that cause the ex-wife to be not entitled to that right.